1994
DOI: 10.1002/ajh.2830470205
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of polycythemia vera among olmsted county, Minnesota residents, 1935–1989

Abstract: To investigate the suggestion that the incidence of polycythemia vera has increased in recent decades, we ascertained secular trends in the incidence of polycythemia vera in Olmsted County, Minnesota, over the 55-year period, 1935-1989. The inpatient and outpatient medical records of all potential cases of polycythemia vera in Olmsted County residents were reviewed and the diagnostic criteria of the Polycythemia Vera Study Group were applied. We found no indication of an increase in the age- and sex-adjusted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
5

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(50 citation statements)
references
References 6 publications
(3 reference statements)
4
41
0
5
Order By: Relevance
“…We also tried to ascertain the clinical impact of median Hct value during the follow-up. Considering the reported PV incidence [1,2], our casistics probably includes more than 50% of PV cases occurred during those years in the city of Turin. Follow-up was fairly accurate, as three patients only were lost and, moreover, all evaluated patients had at least three complete blood counts performed/year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also tried to ascertain the clinical impact of median Hct value during the follow-up. Considering the reported PV incidence [1,2], our casistics probably includes more than 50% of PV cases occurred during those years in the city of Turin. Follow-up was fairly accurate, as three patients only were lost and, moreover, all evaluated patients had at least three complete blood counts performed/year.…”
Section: Discussionmentioning
confidence: 99%
“…Polycythemia vera (PV) is the most common chronic myeloproliferative neoplasm, with an annual incidence of 2.3 per 100,000 [1,2], a reported median survival of 10-15 years [3][4][5][6] and an overall mortality of 3.5 per 100 person/year [5]. Thrombotic complications are the main cause of morbidity and mortality, occurring in more than one third of patients and causing 35-45% of deaths [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous findings, with published data historically supporting a prevalence of females among ET patients and a prevalence of males among patients with PV. [13][14][15][16][17] Gender discrepancies within hematologic malignancies are not unique to MPN. Similar discordances in gender prevalence have been demonstrated in other disorders such as acute lymphoblastic leukemia, chronic lympho-…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18]20,48,49 A study on 831 patients with PV and ET followed for a median time of about 10 years provided evidence that life expectancy of PV patients is reduced when compared with that of the general population, whereas the survival of patients with ET is not significantly shortened. 18 A study from Mayo Clinic including 322 patients with ET followed for a median time of 13.6 years confirmed these data on survival in the first decade of disease and showed that survival became significantly worse thereafter.…”
Section: Life Expectancy In Polycythaemia Vera and Essential Thrombocmentioning
confidence: 99%